Early progressive ambulation in neurosurgical patients with tracheostomy: clinical application and evaluation - Xiangyi Yin; Lihui Zhou; Yan Jia; Xiaowen Zhu (Frontiers in Neurology)
BackgroundTracheostomy is a common procedure among neurosurgical patients, and preventing pulmonary infection while accelerating recovery is crucial for improving their clinical outcomes.ObjectivesThe objective of this study was to systematically assess the efficacy and safety of early progressive ambulation in neurosurgical patients who have undergone tracheostomy, to provide evidence-based insights to guide clinical treatment and nursing practices.MethodsNeurosurgical patients undergoing tracheostomy at our hospital between September 1, 2023, and January 31, 2025 were included. Patients were randomly assigned to either the progressive ambulation group or the routine care group. We established a multidisciplinary team (MDT) led by neurosurgical nurses to develop and implement an early progressive ambulation protocol for neurosurgical patients.ResultsA total of 59 neurosurgical patients who underwent tracheostomy were enrolled, with 29 patients assigned to the progressive ambulation group and 30 patients to the standard routine nursing care group. The findings demonstrate that progressive ambulation offers substantial clinical benefits for neurosurgical patients following tracheostomy. Specifically, this intervention significantly reduces the incidence of pulmonary infections, decreases antimicrobial use density (AUD), and shortens the duration of antibiotic therapy. Furthermore, it is associated with a reduction in the duration of tracheostomy dependency and overall hospital stay, as well as a notable decrease in hospitalization costs. However, no statistically significant difference in mortality was observed.ConclusionThese findings highlight the potential of progressive ambulation as a clinically valuable intervention for improving outcomes in neurosurgical patients undergoing tracheostomy. Further research is necessary to explore its broader applicability across diverse patient populations, identify optimal implementation strategies, and assess long-term effects.